A facile co-precipitation synthesis of novel WO3/NiWO4 nanocomposite with improved photocatalytic activity. (October 2021) - Thilagavathi, T.; Venugopal, D.; Thangaraju, D.; Marnadu, R.; Palanivel, Baskaran; Imran, Mohd; Shkir, Mohd; Ubaidullah, Mohd; AlFaify, S.
Abstract: Herein, we are presenting the synthesis of pure WO3 nanoparticles (NPs) and WO3 /NiWO4 nanocomposites (NCs) with improved photocatalytic activities via a simple co-precipitation process. Structural, morphological, and compositional studies approved the synthesis of the nanocomposite. Furthermore, XPS analysis confirm the chemical composition and incorporation of Ni in the final products. The Scherrer equation used to determine the crystallite size and noticed that it reduced from 34 to 21 nm on Ni added in WO3 and also FESEM study give the average grain size of NPs around 30 nm. HRTEM and SAED studies reveals the nanocomposite phase with lattice spacing of ~0.37 nm, and ~0.29 nm, which is perfectly matched with (020) of WO3 and (111) of NiWO4, respectively. FTIR analysis reveals the functional groups of the formation of WO3 /NiWO4 NCs. Diffused reflectance spectroscopy was employed to determine the energy gap (Eg ) through Kubelka-Munk relation and noticed that the Eg value is reduced from 2.61 to 2.49 eV. PL emission analysis was done under 280 nm excitation and possess the intense emission peaks at 361, 383, 412, and 492 nm, among them 383 nm is high intense, which is originated from near band edge transition. The photocatalytic degradation of Methylene blue (MB) dye was investigated under UV light. The percent degradation of MB dye was observed to be ~70.83%, 71.88%, 76.39%, 86.81% and 90.63% for pure WO3, 5 wt% Ni, 10 wt% Ni, 15 wt% Ni and 20 wt% Ni nanocomposites, respectively. The maximum percent photodegradation of MB dye has been done ∼90.63% for 20 wt% Ni within 80 min of duration. These outcomes revealed that the prepared WO3 /NiWO4 NCs will be highly applicable for hazardous MB dye degradation. Graphical abstract: BET analysis, pseudo-ﬁrst-order kinetic plot for photo-degradation of MB solution and elemental trapping experiment. Image 1 Highlights: Facile synthesis of novel WO3 and WO3 /NiWO4 nanocomposites was attained via low-cost co-precipitation method. XRD, XPS & EDX analyses confirm the synthesis of WO3 and WO3 /NiWO4 nanocomposite. TEM/HRTEM/SAED analyses confirm low dimension spherical NPs synthesis. Energy gap systematically reduced from 2.61 to 2.49 eV on increasing the Ni concentrations in WO3 . Highest photocatalytic degradation of MB dye was noticed for 20% Ni (WO3 /NiWO4 ) specimen.